Spescies of genus Trifolium L. ( Fabaceae Lindl.) in lattakia - العبد, بسام الصالح (Latakia University Journal -Biological Sciences Series, 2020)
This study in 2019, in more than 50 sites, spread over four cities (Lattakia, Al Haffah, Al Qerdaha, Jebleh) of the province of Latakia has shown the presence of 19 Species of genus Trifolium L. (Clover), including several varieties that are considered as new records of Flora plants in Syria. These Species belong to six Sections out of eight according to Zahari (sensu Zohary and Heller, 1984), of which 9 Species belong to the Section Trifolium, which includes Trifolium stellatum L., T. scabrum L., T. cherleri L. , T. lappaceum L., T. arvense L., T. purpureum Loisel., T. echinatum MB, T. scutatum Boiss., T. plebeium Boiss.; and 3 Species belong to the Section Vesicaria Crantz., which includes T. physodes stev. ex M. B., T. resupinatum L., T. tomentosum L.; Moreover, three sectors contained two Species for each. The Section Lotoidea Crantz. included T. nigrescens Viv. and T. repens L., the Section Mistyllus (C. Presl) Godr. included T. spumosum L. and T. argutum Sol., and the Section Trichocephalum Koch included T. pauciflorum D'Urv. and T. subterraneum L.. The study shows that many of those Species that are found in the province has a common distribution, with 12 Species found in 17-30 locations, and 5 Species with limited distribution in 5-10 locations, while two Species T. arvense L. and T. subterraneum L. could be considered as endangered Species in the research area, where each one of them was found only in one location, and the number of their individuals does not occupy more than several square meters.